Interlayer Effect on Connection of Mild Steel ST37 and Stainless Steel 201 on Rotary Friction Welding - Yohanes Yohanes; Muhammad Heriansyah (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
Friction welding is a type of solid state welding where the welding process is carried out in a solid phase to combine various types of ferrous and non-ferrous metals that cannot be welded by the fusion welding method but for welding different metals the welding results are less than optimal due to cracks on the surface of the welding results and differences in mechanical properties that cause the welding result to be brittle, therefore an interlayer is used. In this study, observations were made on the process and results of the joint friction welding using dissimilar metal material between mild steel ST37 and stainless steel 201 with copper interlayer. The results of the test will be a tensile test to see the maximum tensile strength and a hardness test to see the hardness value of the interlayer variation of 0.3 mm, 0.5 mm, 1 mm and without an interlayer. The conclusions obtained are: (1) The effect of the addition of an interlayer on the rotary friction welding process includes the friction phase, the forging phase and the results of welding parameters in the form of motor power, motor angular speed, the change in specimen length is greater without using an interlayer compared to using an interlayer while the duration of welding time is greater using an interlayer than without using an interlayer. (2) The maximum tensile test results were obtained at the 1 mm interlayer at 482.43 MPa and the maximum hardness test results obtained at the 1 mm interlayer were 321.34 VHN.